THE USE OF CLARITY AND AMBIGIUTY IN ACADEMIC WRITING - Maripov Jalolkhan Kamoliddin o’gli; Bahramova Laziza A’zam qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the theory of having precise academic writing . However academic writing serves as fundamental means of communication within the scholarly community , enabling researchers , scholars, and students to convey complex ideas , present findings and engage with existing literature . However the balance between clarity and ambiguity is precarious; effective academic writing must strive for clarity while recognizing that some level of ambiguity is often inherent in complex ideas . This article shows the concepts of clarity and ambiguity and examines strategies for achieving a productive balance , and considers the implication for different academic disciplines .